A highly sensitive electrochemical biosensor for microRNA122 detection based on a target-induced DNA nanostructure. Issue 25 (1st June 2021) - Shen, Ding; Hu, Wei; He, Qiyi; Yang, Huiyi; Cui, Xiping; Zhao, Suqing
Abstract : A highly sensitive electrochemical biosensor employing tetrahedral DNA nanostructure and signal amplification strategies have been constructed, and this method could be used as a universal platform for trace microRNA detection. Abstract : Specific and sensitive biomarker detection is significant for the early diagnosis of cancers. Herein, a highly sensitive electrochemical biosensor employing a tetrahedral DNA nanostructure (TDN) probe and multiple signal amplification strategies has been constructed, and successfully applied to microRNA-122 (miR-122) detection. The platform consisted of a TDN probe anchoring on a gold nanoparticle-coated gold electrode and multiple signal amplification procedures combining the electrodeposition of gold nanoparticles, hybridization chain reaction (HCR), and horseradish peroxidase enzymatic catalysis (HPEC). In the presence of the target, the hairpin structure of the helper probe could be opened and trigger the HCR through the hybridization of H1 and H2 probes, and then avidin–HRP was attached on the surface of the gold electrode that can produce an electro-catalytic signal. We used TDN probe as the scaffold to increase the reactivity and multiple signal amplification greatly improve the sensitivity of this biosensor. This biosensor offers an excellent sensitivity (a limit of detection of 0.74 aM) and differentiation ability for single and multiple mismatches. This multiplexing biosensor for trace microRNA detection shows promising applications in the early diagnosis of cancer.